Wellbore stability and size control: assessing the influence of mixed metal oxide mud using case study methodology - Mohammed Kelany; Nabih A. Alsayed; Ahmed Z. Nooh (Journal of Engineering and Applied Science)
Abstract Oil and gas exploration uses a variety of drilling fluids during the drilling process. The drilling fluid serves to protect the wells and maintain the stability of the borehole. One type of drilling fluid currently used is the so-called mixed metal oxide (MMO) mud. This is a type of drilling mud that is environmentally friendly, biodegradable, non-toxic, and low cost. MMO also provides other functions such as hole cleaning, lubrication, cooling, hydraulic lifting, and borehole stabilizing. However, some effects of this type of fluid on the drilling process are still unknown, such as the effect of MMO on the borehole size. This research evaluates the impact of MMO mud on borehole sizes. To understand this effect, a case study was performed using two wells/sections, one drilled with MMO mud and the other with conventional polymer mud. The case study has been performed, including wells located in the same field and with the same formation layers, to isolate the other factors that affect the borehole size, including formation types, local field stresses, and drilling techniques. The results can improve calculations for borehole size in case using MMO mud instead of the conventional polymer mud. The results showed an 11% increase from the theoretical calculation. This important finding is essential for drilling-related calculations, including but not limited to cement calculations and bottom hole assembly (BHA) performance.